Correction to: Relationship of living arrangement with the decline in functional capacity in elderly people by gender: a longitudinal observational study - Haruhiko Imamura; Eiko Uchiyama; Miki Akiyama; Ikuyo Kaneko; Toru Takebayashi; Yuji Nishiwaki (Komiyama Printing Co. Ltd, 2020)
An amendment to this paper has been published and can be accessed via the original article.